A Synthesized Glucocorticoid- Induced Leucine Zipper Peptide Inhibits Retinal Müller Cell Gliosis - Ruiping Gu; Xinyi Ding; Wenyi Tang; Boya Lei; Chen Jiang; Gezhi Xu; Gezhi Xu; Gezhi Xu (Frontiers Media S.A., 2018)
Purpose: The anti-inflammatory activities of protein glucocorticoid-induced leucine zipper (GILZ) have been demonstrated in vivo and in vitro. Here, we examined the potential effect of a synthetic peptide derived from the leucine zipper motif and proline-rich region of GILZ on suppressing inflammatory responses in primary cultured rat Müller cells.Methods: Peptides were selected from amino acids 98-134 of the GILZ protein (GILZ-p). Solid-phase peptide synthesis was used to generate the cell-penetrating peptide TAT, which was bound to the amino terminus of GILZ-p. Primary cultured retinal Müller cells were stimulated with lipopolysaccharide (LPS) alone or in combination with different concentrations of GILZ-p, and the interaction of GILZ-p with nuclear factor (NF)-κB p65 in Müller cells was investigated by western blotting, immunoprecipitation, and immunofluorescence. The expression of the Müller cell gliosis marker glial fibrillary acidic protein (GFAP), functional protein aquaporin (AQP)-4, and the inflammatory cytokines interleukin (IL)-1β, tumor necrosis factor (TNF) α, intercellular adhesion molecule (ICAM)-1, and monocyte chemoattractant protein (MCP)-1 was measured by Western Blotting. The concentration of those cytokines in culture medium was measured by using Enzyme-Linked Immunosorbent Assay.Results: The synthesized GILZ-p, which was water-soluble, entered cells and bound with NF-κB p65, inhibiting p65 nuclear translocation. GILZ-p inhibited the LPS-induced expression of GFAP, IL-1β, TNFα, ICAM-1, and MCP-1 in Müller cells and prevented the LPS-induced downregulation of AQP4.Conclusions: These results indicate that GILZ-p interacted with NF-κB p65 and suppressed p65 nuclear translocation, thereby inhibiting inflammatory cytokine release and Müller cell gliosis.